Analysis and optimization of flow module frame using finite element analysis (FEA) - Chua, Yek Guo (2015)
The frame of the flow module is designed to hold various components, such as choke and flow meter, and take the stress loading present during lifting, installation and retrieval. This structure had to be designed to ensure its structural integrity throughout its lifespan. With today’s technology, products are designed virtually using computational software, also tested in virtual environment and conditions to simulate real world operation and loading cases. These process and tools produce advantageous characteristics on products that make them more reliable and resources efficient. In this project, we will study on Subsea Christmas Tree’s Flow Module Frame, which is vital in ensuring safe and reliable oil production from subsea well. The aim of this project is to determine the structural integrity of this structure with static structural analysis using simulated finite element analysis (FEA). The results for the maximum deformation and Von-mises stress of the frame under designated load are studied and discussed. Hereby, we can determine if this design of flow module frame is viable and appropriate.